ChemInform Abstract: On the Fluorination of Plutonium Dioxide by Ammonium Hydrogen Fluoride. Issue 21 (6th May 2016) - Claux, Benoit; Benes, Ondrej; Capelli, Elisa; Soucek, Pavel; Meier, Roland
Abstract: Following a literature survey on published PuF3 syntheses in view of its use within the fuel cycle of advanced molten salt fast nuclear reactors, the authors′ own method comprises fluorination of PuO2 with NH4 HF2 (Ni crucible in stainless steel container, 350 °C, 24 h, 92% yield).